PENGARUH TRUST TERHADAP ONLINE REPURCHASE INTENTION DENGAN E-SATISFACTION SEBAGAI VARIABEL MEDIASI: STUDI PADA GENERASI MILENIAL PENGGUNA TOKOPEDIA - Farisa Novita Puri; Fransisca Mulyono (Journal of Management Small and Medium Enterprises (SMEs), 2023)
This study aims to examine the influence of trust to repurchase intention with e-satisfaction as a mediating variable. This study uses an online survey designed to collect data from the millennial generation who have made at least two purchases at Tokopedia. A total of 113 responses were considered valid, for data analysis using the SEM-PLS approach. Overall, the findings show that there is no direct significant relationship between trust and repurchase intention. In an indirect relationship, trust has a positive and significant effect on repurchase intention through e-satisfaction. This finding reveals that trust is an important factor in creating e-satisfaction with online shopping and consequently increases the repurchase intention at Tokopedia. Keywords: Trust; E-satisfaction; Repurchase Intention